Studies On Binder Creep, Abrasion Loss And Dynamic Stripping Of Porous Asphalt - Hasan, Mohd Rosli Mohd (2011)

(untitled)
After several years in service, porous asphalt looses permeability primarily due to clogging. This study presents a phenomenon postulated as binder creep, as another source of permeability loss in porous asphalt. To ascertain the binder creep, samples were separately conditioned at 15oC, 20oC, 30oC and 35oC. Permeability measurements were carried out at regular intervals up to 120 days using a falling head water permeameter. Apart from clogging, the most serious problem that limits porous asphalt durability and service life is ravelling.